Faktor-faktor yang mempengaruhi efektivitas organisasi pembantu Bupati :: Kasus organisasi pembantu Bupati Kapuas Wilayah Pulang Pisau di Kabupaten Daerah Tingkat II Kapuas - SALAMPAK, SALAMPAK (Universitas Gadjah Mada, 1998)
Rule Number 5 Year 1974 through article 73 enables to form an organization for assistant regent by considering volume dan various &airs performed by regional heads, geographicaI/area situations, region and control extension. Based on domestic Minister Number : 821-26-199, dated February 25, 1982, the assistant regen of Kapuas, area of Pulang Pisau, and through governor decision of local head of level I (DATI I) of Central M imantan Number : 061.1/294/Huk7the organizational structure and its procedure, leading to domestic Minister’s decision Number: 132 Y a 1978, with major t s assisting the regent er ak of local head of level I1 of Kapuas, in coordinating, controlling and guiding the general government and development performed by subdistrict government, in regional work environment and other government affairs, in order to perform t e deconcentrated principle, h were established. The organization effectiveness of assistant regent of Kapuas, area of Pulang Pisau, t today, is still low, a least viewed from productivity, flexibility, and job satis@on. The productivity is seen from coordination performance, control and performance guidance of government and development have not been done maximally yet, due to unclear function limitation task of local head given to “its assistant,’ existing in region, so that is results in doubt in performing task, even it overlaps. The rate of flexibility becomes low because the power of organization is low, as result, t dependence on organization existing in the upper is he higher and tends to be centralist. The rate of job satisfixtion of low level workers, signed by the lower motivation, viewed from the job activity in every work hour, rate of official movement or reward obtained in the dedication. T e f$ctors affecting organization, consistent with the characteristics, can be viewed h from the following two fbctors, internal and external factors. Internally, the effectiveness of organization is affected by apparatus resources (personnel) that is relatively lower, observed from average formal education of workers stiU dominated by the lower-High School (75%) education, relatively lower education of structural position hohiers, and minimum education and job functional training ever followed by workers. The organizational structure, which is no longer consistent, by developing and more emphasizing consistence with government t s , ak but less providing service to people. The condition is even increased by minimum instruments and operational funds in supportmg the activities. Externally, the organization effectiveness is the effected by what to extent the upper government (especially regent of local head) and vertical in&mce/service. Attentions and support, espesially from regent of local head, in developing the function of organization, are relatively lower, that can be viewed from task subdistrict head organization, job adoption and retirement, reportug, o direct task r responsibility are done by and delivered to the regent of local head. The suppodservice of instance of regency level, are relatively lower and lack of involving assistant regent in controlhg and guiding program/activty in area of work. In order organization effectiveness increases, it is necessary to regulate task and function by delegating more sufficient power of the regent og local head, review the organizational structme to be more adaptive and capable of providing service to people and more chances for increasing apparatus resources.